Older worker trends - Axley, Leonard E. (Nova Science Publishers, 2009)
Focuses on changes during the period 1990-2008 in the labour force participation rates of Americans aged 55 to 64 and older. Examines the role of self-employment in the retirement process and the expected shift in the demographic profile of the work force.